2008
DOI: 10.3892/or.19.6.1565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cranberry juice concentrate on chemically-induced urinary bladder cancers

Abstract: Abstract. The chemopreventive efficacy of cranberry juice concentrate in an experimental model of urinary bladder cancer was evaluated using female Fischer-344 rats. The animals received N-butyl-N-(4-hydroxybutyl)-nitrosamine (OH-BBN) for a period of eight weeks. Cranberry juice concentrate was administered at doses of 1.0 or 0.5 ml/rat/ day beginning one week after the final OH-BBN treatment and continuing until the end of the study. The urinary bladders of all the rats were weighed and examined grossly for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…An in vivo experiment in rats demonstrated that treatment with cranberry juice concentrate extracted with ethyl acetate at doses of 1.0 and/or 0.5 mL/day over six weeks resulted in a significant decrease in the number and size of urinary BC tumours. Upon treatment, ACNs and PACs were detected in the serum and urine samples, while no Qu was observed, suggesting its low bioavailability [53]. The anticancer effects of cranberryderived flavonoids were evaluated in an in vivo model of BC.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…An in vivo experiment in rats demonstrated that treatment with cranberry juice concentrate extracted with ethyl acetate at doses of 1.0 and/or 0.5 mL/day over six weeks resulted in a significant decrease in the number and size of urinary BC tumours. Upon treatment, ACNs and PACs were detected in the serum and urine samples, while no Qu was observed, suggesting its low bioavailability [53]. The anticancer effects of cranberryderived flavonoids were evaluated in an in vivo model of BC.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The primary components of cranberry are water, organic acids (including salicylate), fructose, vitamin C, flavonoids, anthocyanidins, catechins, and triterpenoids. An animal study involving Fischer-344 female rats demonstrated the confirmed effectiveness of cranberry juice concentrate in preventing urinary bladder cancers induced by N-butyl-N-(4-hydroxybutyl)-nitrosamine [33]. The anticancer properties of cranberries may involve impaired angiogenesis through the inhibition of VEGF-associated blood vessel formation, thus preventing tumor growth [34].…”
Section: The Relationship Between the Development Of Bladder Cancer A...mentioning
confidence: 99%
“…Moreover, cranberry is known to possess various flavonoids, with quercetin 3-Ogalactoside being the predominant compound in fruit powder [33]. Quercetin has been extensively studied for its potential anti-cancer effects [56,57].…”
Section: The Relationship Between the Development Of Bladder Cancer A...mentioning
confidence: 99%